Tension-Free Vaginal Tape for The Treatment of Stress Urinary Incontinence: The Paraurethral Approach - Akın Sivaslıoğlu; İsmail Dölen; Berfu Demir; Orhan Gelişen; Serdar Dilbaz; Eylem Ünlübilgin; Ali Haberal (Medical Network, 2006)
OBJECTIVE: To evaluate the efficiency of the paraurethral approach tension-free vaginal tape for the treatment of stress urinary incontinence. STUDY DESIGN: The study was carried out in the urogynecology department of Ministry of Health Ankara Etlik Maternity and Women's Health Teaching Research Hospital. Fifty -two women who were diagnosed as having stress urinary incontinence (SI) were enrolled in this prospective study. The paraurethral tension free vaginal tape operation was performed for the treatment of stress urinary incontinence. RESULTS: The mean follow up period was 36 months. Objective cure was accomplished in 46 patients (88.5%), partial recovery was seen in 2 patients (3.8%), complete failure was observed in 4 patients (7.7 %). Bladder perforation occurred in 2 patients (3.8%), Retzius hematoma developed in 1 patient (1.9%). Also, tape erosion was observed in 4 patients (7.7%), on the follow up period. CONCLUSION:The paraurethral tension free vaginal tape operation is an efficient antiincontinence surgery .